FORMATION OF STUDENTS-PSYCHOLOGISTS «SOFT SKILLS» AS A FACTOR OF THEIR SUCCESSFUL FUTURE PROFESSIONAL ACTIVITY (Psychology Travelogs, 2021)
The article considers the problem of forming «soft skills» in students-psychologists as a necessary component of their future professional activity. Based on the analysis of theoretical data, the authors of the article found that «soft skills» is a set of personality traits, social skills, communication skills, personal habits, friendliness and optimism. This group of skills includes individual, communication and management skills. The article finds that «soft skills» are in addition to «hard» or «professional» skills («hard skills»), but in contrast to «hard skills», which can be formed and developed, «soft skills» are more difficult to master and change.The authors of the article identified five groups of «soft skills» of future specialists in the field of psychology, which are an important component of their successful professional activity: communication skills, personal effectiveness skills, management skills, strategic skills and critical thinking. Communication skills are an important professional and personal quality of a future psychologist. This group includes such competencies as: the ability to work in a team, negotiation, the ability to communicate effectively with colleagues, clients, managers, interpersonal communication, the ability to persuade, resolve conflict situations, make independent decisions. Personal performance skills, which include time management competencies or time management, responsibility, resilience, ability to achieve goals, creativity and analytical thinking. Management skills are competencies for working in a multidisciplinary team. Critical thinking is one of the most important skills of the 21st century. The future specialist in the field of psychology must be able to analyze, systematize, evaluate data and more.Based on the analysis of theoretical sources, the authors of the article characterize the ways of development of selected groups of «soft skills» in future psychologists.
Keywords: soft skills; hard skills; psychologist; professional activity; students; institution of higher education